Latency-driven distribution infrastructure needs of participatory entertainment applications. - Safaei, Farzad (IEEE Communications magazine)
This article evaluates network and server infrastructure requirements to support real-time flows associated with networked entertainment applications. These include the state information flow to update the status of the virtual environment and immersive communication flows such as voice, video, gesture, and haptics communication. The article demonstrates that scaling these applications to large geographical spreads of participants requires distribution of computation to meet the latency constraints of the applications. This latency-driven distribution of computation is essential even when there are no limitations on the availability of computational resources in one location. The article provides detailed results on distributed server architectures for two of these real-time flows, state information and immersive voice communication. It also identifies a generic set of requirements for the underlying network and server infrastructure to support these applications and propose a new design, called switched overlay networks, for this purpose.